1998
DOI: 10.1143/jjap.37.5112
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Annealing Temperatures and Ambient Atmospheres on the Electrical Properties of Ultrathin (Ba,Sr)TiO3 Capacitors

Abstract: Ultrathin (Ba,Sr)TiO3 (BST) film capacitors with a Pt/Ba0.5Sr0.5TiO3(30 nm)/Pt/TiN/Si structure were fabricated. To investigate the effects of annealing temperatures, capacitors were annealed in flowing Ar or O2 at temperatures ranging from 400°C to 600°C for 30 min. The electrical properties of the annealed samples were strongly dependent on the annealing temperatures. In the capacitors annealed at 500°C (in Ar and O2) and 550°C (in O2), the leakage current decreased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the literature, it has been shown that leakage characteristics and Schottky barrier heights in Pt/perovskite structures are sensitive to annealing and deposition conditions [27,[29][30][31][32]. In particular, it has been established that oxygen anneals reduced high field leakage, whereas forming gas (hydrogen) anneals increased high-field leakage in SrTiO 3 and BST films with Pt electrodes.…”
Section: B Room Temperature Dielectric Properties Of Films With Diffmentioning
confidence: 99%
“…In the literature, it has been shown that leakage characteristics and Schottky barrier heights in Pt/perovskite structures are sensitive to annealing and deposition conditions [27,[29][30][31][32]. In particular, it has been established that oxygen anneals reduced high field leakage, whereas forming gas (hydrogen) anneals increased high-field leakage in SrTiO 3 and BST films with Pt electrodes.…”
Section: B Room Temperature Dielectric Properties Of Films With Diffmentioning
confidence: 99%